2020
DOI: 10.1007/s00213-020-05678-7
|View full text |Cite
|
Sign up to set email alerts
|

N-acylethanolamine acid amidase (NAAA) inhibition decreases the motivation for alcohol in Marchigian Sardinian alcohol-preferring rats

Abstract: Rationale-N-acylethanolamine acid amidase (NAAA) is an intracellular cysteine hydrolase that terminates the biological actions of oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), two endogenous lipid-derived agonists of the nuclear receptor, peroxisome proliferator-activated receptor-α. OEA and PEA are important regulators of energy balance, pain and inflammation, but recent evidence suggests that they might also contribute to the control of reward-related behaviors.Objectives and Methods-In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Thus, at a group level, increased lever pressing during FR sessions was associated with increased lever pressing during progressive ratio sessions. Although FR1 and FR2 are low effort schedules of reinforcement and are typically considered a measure of consummatory behavior rather than motivation (Arnold & Roberts, 1997), our data are consistent with other studies reporting a consistency between fixed ratio and progressive ratio measures of reward's motivational properties (Fotio et al, 2021;Velázquez-Sánchez et al, 2014). As regards FR5, it has been proposed as a moderate-effort schedule measuring both intake and motivation (Vendruscolo et al, 2010), therefore the consistency found here between FR5 and PR3 is in support of this idea.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, at a group level, increased lever pressing during FR sessions was associated with increased lever pressing during progressive ratio sessions. Although FR1 and FR2 are low effort schedules of reinforcement and are typically considered a measure of consummatory behavior rather than motivation (Arnold & Roberts, 1997), our data are consistent with other studies reporting a consistency between fixed ratio and progressive ratio measures of reward's motivational properties (Fotio et al, 2021;Velázquez-Sánchez et al, 2014). As regards FR5, it has been proposed as a moderate-effort schedule measuring both intake and motivation (Vendruscolo et al, 2010), therefore the consistency found here between FR5 and PR3 is in support of this idea.…”
Section: Discussionsupporting
confidence: 91%
“…One potential limitation of the study is that we used a strain of rats that has a genetically determined preference for alcohol. Although widely used in alcohol research (Economidou et al, 2006;Stopponi et al, 2013Stopponi et al, , 2018Kirson et al, 2018;Logrip et al, 2018;Domi et al, 2019a;Borruto et al, 2020;Fotio et al, 2020aFotio et al, , 2020b, this strain is characterized by the inherent limitation of being a genetic model that likely mimics a specific form of AUD. However, in a recent study we also reported that activation of PPARγ reduces alcohol drinking in nonselected rats and mice suggesting a more general role of this receptor system in AUD (Domi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Self-administration experiments were conducted according to our recent reports (Stopponi et al, 2018;Fotio et al, 2020aFotio et al, , 2020b using standard operant chambers (Med Associate, St Albans, VT) located in sound-attenuating, ventilated cubicles. Each chamber was equipped with a drinking reservoir (volume capacity: 0.30 ml) positioned 4 cm above the grid floor in the center of the front panel of the chamber.…”
Section: Operant Self-administrationmentioning
confidence: 99%
“…NAAA is believed to primarily control PEA levels and has been proposed as an alternative target for activation of PEA/ PPARα signaling (Tsuboi et al, 2005;Tai et al, 2012;Bottemanne et al, 2018). To date, many potent NAAA inhibitors have been developed, some of them were observed to elevate PEA levels and exhibit potent anti-inflammatory and analgesic effects in a range of rodent models of human disease (Alhouayek et al, 2015;Bonezzi et al, 2016;Alhouayek et al, 2017;Bottemanne et al, 2018;Sagheddu et al, 2019;Fotio et al, 2020;Piomelli et al, 2020;Sgroi et al, 2021). However, the impact of NAAA on AEA and OEA degradation has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%